Benefits of supervised community physical activity in obstructive sleep apnoea. Issue 5 (22nd November 2018) - Berger, Mathieu; Barthélémy, Jean-Claude; Hupin, David; Raffin, Jérémy; Dupré, Caroline; Labeix, Pierre; Costes, Frédéric; Gaspoz, Jean-Michel; Roche, Frédéric
Obstructive sleep apnoea (OSA) is a chronic disorder characterised by repetitive episodes of partial or complete airway obstruction occurring during sleep [1]. Recent data suggest that moderate-to-severe OSA is highly prevalent, affecting up to 50% of males and 25% of females [2]. OSA is associated with frequent cardiovascular and cerebrovascular events [3]. Although continuous positive airway pressure (CPAP) is the gold standard treatment, long-term adherence remains poor, particularly in moderate and in non-sleepy patients [4], while the cardiovascular risk remains high. Long-term physical activity programmes outside of hospitals may help improve moderate obstructive sleep apnoea, particularly in obese patients http://ow.ly/11jg30lOJYS